Sensory profile and preference mapping of orange cakes with addition of prebiotics inulin and oligofructose - Volpini-Rapina, Larissa Fernanda [UNESP]; Sokei, Fabiana Ruriko [UNESP]; Conti-Silva, Ana Carolina [UNESP] (Elsevier, 2012)
Orange cakes with addition of inulin and oligofructose to justify a prebiotic claim (minimum of 3 g of fructans in a 60 g serving of cake) were investigated regarding sensory aspects. The sensory profile of cakes with inulin, with inulin/oligofructose and without prebiotics (standard cake) was evaluated using descriptive quantitative analysis. Preference mapping was assessed using multidimensional scaling on data obtained through an acceptability test with a nine-point hedonic scale. The cakes with prebiotics presented greater crust brownness, dough beigeness, hardness and stickiness than the standard cake and lower crumbliness. Principal Component Analysis (69.5 and 10.7% of explanation to the first and second principal components, respectively) showed that crust brownness, dough beigeness, hardness and stickiness contributed to distinguish the cakes with prebiotics from standard cakes. The sensory acceptability was similar for the three cakes and higher when compared to three commercial cakes, but the preference mapping showed that cakes with prebiotics were preferred to commercial cakes. Addition of prebiotics in orange cakes is feasible, based on the sensory results, which may facilitate marketing of this functional food with sensorial qualities equivalent to conventional products. © 2012 Elsevier Ltd.
Keywords: Descriptive quantitative analysis; Multidimensional scaling; Orange cake; Prebiotics; Preference mapping; Conventional products; Fructans; Functional foods; Multi-dimensional scaling; Oligo-fructose; Principal Components; Sensorial qualities; Sensory profiles; Hardness; Polysaccharides; Principal component analysis; Standards; Mapping